Direct fabrication of complex 3D hierarchical nanostructures by reactive ion etching of hollow sphere colloidal crystals. Issue 35 (22nd August 2016) - Zhong, Kuo; Li, Jiaqi; Van Cleuvenbergen, Stijn; Clays, Koen
Abstract : A straightforward hollow sphere colloidal lithography was developed to directly produce complex 3D hierarchical nanostructures. Abstract : Direct reactive ion etching (RIE) of hollow SiO2 sphere colloidal crystals (HSCCs) is employed as a facile, low-cost method to fabricate complex three-dimensional (3D) hierarchical nanostructures. These multilayered structures are gradually transformed into nanostructures of increasing complexity by controlling the etching time, without complicated procedures (no mask needed). The resulting 3D topologies are unique, and cannot be obtained through traditional approaches. The formation mechanism of these structures is explained in detail by geometrical modeling during the different etching stages, through shadow effects of the higher layers. SEM images confirm the modeled morphological changes. The nanostructures obtained by our approach show very fine features as small as ∼30 nm. Our approach opens new avenues to directly obtain complex 3D nanostructures from colloidal crystals and can find applications in sensing, templating, and catalysis where fine tuning the specific surface might be critical.